Genetic association between HLA-G 14-bp polymorphism and diseases: A systematic review and meta-analysis - de Almeida, Bibiana Sgorla (2018)
Background: HLA-G is an immune checkpoint molecule. Since a differential molecule expression has been reported even for healthy individuals, many studies have focused on polymorphisms at HLA-G regulatory regions, particularly the 3′ untranslated region (3′UTR). The presence/absence of a 14-bp sequence was the first polymorphism described and it is the most studied in association between HLA-G and disorders. Methods: In this study, we performed a systematic review and meta-analysis of all association studies published regarding the HLA-G 14-bp. Results: We verified association between 14-bp alleles and diseases in the following situations: (1) presence of 14-bp (insertion) conferred susceptibility to preeclampsia (child alleles evaluated) and systemic lupus erythematosus (OR = 1.42; 95%CI = 1.04–1.93; p = 0.026 and OR = 1.13; 95%CI = 1.01–1.27, p = 0.028); (2) 14-bp absence (deletion) was associated with increased risk to breast cancer (OR = 1.23; 95%CI = 1.06–1.43; p = 0.006) and human Cytomegalovirus infection (OR = 2.06; 95%CI = 1.60–2.64; p < 0.0001); and (3) a risk association was observed between the group of reproductive disorders and the 14-bp insertion (OR = 1.12; 95%CI = 1.01–1.24; p = 0.034). Conclusions: Considering that others 14-bp associations were inconclusive and that other variation sites observed at HLA-G 3′UTR exhibit a proven role on post-transcriptional regulation of HLA-G expression, the complete 3′UTR segment should be analyzed in terms of disease susceptibility, instead of a single polymorphism.